Pulsed-wave Doppler ultrasonographic evaluation of hepatic vein in dogs with tricuspid regurgitation - Kim, Jaehwan (J Vet Sci, 2017)
This study was performed to identify the relationships between hepatic vein (HV) measurements, including flow velocity and waveform, using pulsed-wave (PW) Doppler ultrasonography, and the severity of tricuspid regurgitation (TR) in dogs. The study included 22 dogs with TR and 7 healthy dogs. The TR group was subdivided into 3 groups according to TR jet profile obtained by echocardiography. The hepatic venous waveform was obtained and classified into 3 types. A variety of HV measurements, including the maximal velocities of the atrial systolic, systolic (S), end ventricular systolic, and diastolic (D) waves and the ratio of the S- and D- wave velocities (S/D ratio), were acquired. TR severity was significantly correlated with the S- (r = −0.380, p = 0.042) and D- (r = 0.468, p = 0.011) wave velocities and the S/D ratio (r = −0.747, p < 0.001). Receiver operating characteristic curve analysis revealed the highest sensitivity and specificity for the S/D ratio (89% and 75%, respectively) at a threshold of 0.97 with excellent accuracy (AUC = 0.911, p < 0.001). In conclusion, PW Doppler ultrasonography of the HV can be used to identify the presence of significant TR and to classify TR severity in dogs.